2011
DOI: 10.1088/0964-1726/20/5/055019
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of energy harvesting from renewable sources with PVDF and PZT

Abstract: Piezoelectric materials have been in use for many years; however, with an increasing concern about global warming, piezoelectricity has gained significant importance in research and development for extracting energy from the environment. In this work the voltage responses of ceramic based piezoelectric fibre composite structures (PFCs) and polymer based piezoelectric strips, PVDF (polyvinylidene fluoride), were evaluated when subjected to various wind speeds and water droplets in order to investigate the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(142 citation statements)
references
References 25 publications
1
139
0
2
Order By: Relevance
“…Another attempt to harvest energy from human body motion was by Granstrom et al [8] where these researchers embedded piezoelectric PVDF films into the straps of a backpack. Li et al [2] and Vatansever et al [9] demonstrated that piezoelectric PVDF can be used to generate a continuous power of the order of 100 µW using wind energy at moderate wind speeds. Most of the earlier research reported that ceramic based piezoelectric structures generated higher voltage than the piezoelectric PVDF structures [10] [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another attempt to harvest energy from human body motion was by Granstrom et al [8] where these researchers embedded piezoelectric PVDF films into the straps of a backpack. Li et al [2] and Vatansever et al [9] demonstrated that piezoelectric PVDF can be used to generate a continuous power of the order of 100 µW using wind energy at moderate wind speeds. Most of the earlier research reported that ceramic based piezoelectric structures generated higher voltage than the piezoelectric PVDF structures [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the earlier research reported that ceramic based piezoelectric structures generated higher voltage than the piezoelectric PVDF structures [10] [11]. Vatansever et al [9] have recently demonstrated that under certain conditions such as generation of energy from the wind and rain, piezoelectric PVDF generated higher voltage and power compared to ceramic based PZT and Piezoelectric Fibre Composite (PFC) structures. One of the reason is due to the lower stiffness (low resonance frequency) of the PVDF structures.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 lists the major properties of the adopted piezoelectric material for piezo patches. It should be noted that in Figure 11a, phase difference exists obviously between the C l p and responding voltage responses due to the partial derivative term with respect to time in Equation (7). Nevertheless, their fluctuation frequencies remain the same, which equals the vortex shedding frequency.…”
Section: Output Voltagementioning
confidence: 92%
“…Pobering and Schwesinger [5] conducted research on the ability of a PVDF (polyvinylidene fluoride) flag, similar to the 'eel' created by Taylor et al Their converter could be combined with other alternative power sources without any maintenance. By means of PVDF films used as a cantilever [6,7] or attached to a leaf-shaped structure [8], wind-energy harvesters with piezoelectric material have also been investigated. Akaydin et al [9] experimented the wake of a circular cylinder through the output voltage of a piezoelectric cantilever beam, in which the cantilever is parallel to the incoming flow and cantilevered at its downstream end.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are gaining popularity due to vast applications ranging from electronics to biomedical areas (Dang et al 2003;Thakur et al 2012;and Xu et al 2011). Polymers which are electro active have wide scope in piezoelectric energy harvesting applications (Vatansever et al 2011). PVDF is electro active polymer having strong piezoelectric properties and utilized in many engineering applications from capacitor to complicated tactile sensor (Damaraju et al 2013;and Sencadas et al 2012).…”
Section: Introductionmentioning
confidence: 99%